Hegemoni Kekuasaan Pada Novel “Si Putih” Karya Tere Liye (Teori Gramsci) - Anisa Triana Octavia; Nazwa Rahmawati; Supriyono Supriyono (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to examine the form of hegemony of power contained in the novel "Si Putih" by Tere Liye. This research uses Gramsci's Hegemony theory. The research method used is descriptive qualitative with a literary research approach with literature study data collection techniques, reading techniques and note-taking techniques. The data source of this research comes from the novel "Si Putih" by Tere Liye published in 2021 by Gramedia Pustaka Utama in the form of phrases, sentences or paragraphs contained in the novel. The results of this study describe the form of hegemony of power in the story towards the end of the novel "Si Putih" in one of the characters, namely the King of Mount Timur. The form of hegemony of power he exercised was to subjugate the Animal Controller to submit under his rule. In addition, the Eastern Mountain King's form of hegemony is shown by utilizing the power he has, by releasing the virus to modern cities so that his goal of revenge is achieved.